Insularity and Identity in the Roman Mediterranean - Purcell, Nicholas (Oxbow Books, Limited, 2017)
Cover -- Book Title -- Copyright -- Contents -- About the Authors -- Preface: Anna Kouremenos -- 1. Introduction: Anna Kouremenos -- 2. Insularity and Identity in Roman Cyprus: Connectivity, Complexity, and Cultural Change: Jody Michael Gordon -- 3. In the Heart of the Wine-dark Sea: Cretan Insularity and Identity in the Roman Period: Anna Kouremenos -- 4. Insularity and Identity in the Northern Sporades Islands: The Question of Roman Policy in Central Greece: Alkiviadis A. Ginalis -- 5. Where East Meets West: Island Societies of the Ionian Sea Under Roman Rule: Sophia Zoumbaki -- 6. The Cult of Silvanus in the Central Adriatic Islands between Insularity and Connectivity: Danijel Dzino -- 7. Tracing Identity from Insularity: Maltese Industries in the Late Punic and Roman Period: Maxine Anastasi -- 8. Connectivity, Trade and Punic Persistence: Insularity and Identity in Late Punic to Roman Republican Sardinia (3rd-1st century BC): Andrea Roppa -- 9. Etudes et constat préliminaire des implantations fortifiées de Corse du second âge du Fer au changement d'ère. Le Cas de la région Centre-Ouest de la Corse: Jean-Baptiste Mary -- 10. Conclusion: Swii Yii Lim -- Index.